Effect of organic matrices on the determination of the trace element chemistry (Mg, Sr, Mg/Ca, Sr/Ca) of aragonitic bivalve shells (Arctica islandica)—Comparison of ICP-OES and LA-ICP-MS data - Schöne, Bernd R. (2010)
The element chemistry of biogenic carbonates can provide important data on past environments. However, the Sr/Ca and Mg/Ca ratios as well as the Mg and Sr concentrations of biological carbonates, especially aragonitic bivalves often depart from apparent thermodynamic equilibrium. When measured in situ by means of LA-ICP-MS, the Mg concentration is often substantially enriched (two- to threefold) near the organic-rich, annual growth lines. To test the hypothesis thatsome organic components exert a major influence on the skeletal metal content, the element chemistry of different shell components (insoluble organic matrix, IOM; dissolved CaCO3 and soluble organics, SOM) of Arctica islandica was measured by means of ICP-OES and LA-ICP-MS. The ICP-OES data indicate that the IOM is strongly enriched in Mg (130ppm) and depleted in Sr and Ca (10 ppm and 0.22 wt%, respectively) when compared to the whole biomineral (Mg: 68 to 99 ppm, Sr: 860 to 1,060 ppm, Ca: ~35.72 wt%). Although the average relative abundance of the IOM barely exceeds 0.46 wt%, its chemical composition in combination with its heterogeneous distribution across the shell can significantly increaseestimates of the Mg concentration if measured in situ by LA-ICP-MS. Depending on the distribution of the IOM, the Ca concentration may be significantly lower locally than the average Ca concentration of the whole shell (35.72 wt%). If this remains undetected, the Mg concentration of shell portions with higher than average IOM content is overestimatedby LA-ICP-MS and, conversely, the Mg concentration is underestimated in shell portions with lower than average IOM content. Removal of the IOM prior to the chemical analysis by LA-ICP-MS or mathematical correction for the IOM derived magnesium concentrations is therefore strongly advised. The different chemistry of the IOM may also exert amajor control on the trace element to calcium ratios. Shell portions enriched in IOM will show up to 200 times higher Mg/Ca and up to two times higher Sr/Ca ratios than the average shell of A. islandica. Without removal of the IOM prior to the analysis, Mg/Ca and Sr/Ca ratios of shell portions with higher IOM content cannot be used as paleothermometers. Because it is currently impossible to remove the IOM prior to chemical analyses by LA-ICP-MS, we recommend the use of wet chemical techniques (= possibility to separate and measure individual shell components) such as ICP-OES at the expense of lower sampling resolution. The results of this study will significantly improve our understanding of shellbased climate and environmental proxies.